ICD-11-Based Assessment of Social Media Use Disorder in Adolescents: Development and Validation of the Social Media Use Disorder Scale for Adolescents - Paschke, Kerstin; Austermann, Maria Isabella; Thomasius, Rainer (Frontiers in Psychiatry, 2021)
Background: A problematic social media use (PSMU) in adolescents is a rising phenomenon often associated with higher perception of psychological stress and comorbid psychiatric disorders like depression. Since the ICD-11 introduced the very first internet-use related disorders, criteria for gaming (and online gambling) disorder can now be transferred to assess social media use disorder (SMUD). Therefore, the development and validation of a self-rating screening instrument for SMUD is of value to researchers and clinicians. Method: The previously validated ICD-11-based Gaming Disorder Scale for Adolescents (GADIS-A) was adapted to measure SMUD (Social Media Use Disorder Scale for Adolescents, SOMEDIS-A). A representative sample of 931 adolescents aged 10 to 17 years and a respective parent participated in an online study. Item structure was evaluated by factorial analyses. Validated DSM-5-based instruments to assess PSMU by self- and parental ratings (SMDS, SMDS-P), adolescent depressive symptoms (PHQ-9), and stress perception (PSS-10) as well as single items on time spent with social media (SM, frequency and duration) were applied to assess criterion validity. Discrimination between pathological and non-pathological users was examined based on ROC analyses retrieved cut-off values and the results of a latent profile analysis. Results: The new scale is best described by two factors reflecting cognitive-behavioral symptoms and associated negative consequences. The internal consistency was good to excellent. The SOMEDIS-A-sum score was positively correlated with PSMU, depression, and stress scores as well as the time spent with SM in a moderately to highly significant manner. Thus, good to excellent criterion validity is suggested. Conclusions: SOMEDIS-A is the first successfully validated instrument to assess SMUD in adolescents based on the ICD-11 criteria of GD. Thus, it can support early detection in order to prevent symptom aggravation, chronification, and secondary comorbidities. It can contribute to the development of a standardized conceptualization and its two-factorial structure offers promising new insights into the evaluation of SM usage patterns. Further examination including clinical validation is desirable.